Hydroxylated Multi‐Walled Carbon Nanotubes Covalently Modified with Tris(hydroxypropyl) Phosphine as a Functional Interlayer for Advanced Lithium–Sulfur Batteries. (11th May 2022) - Yang, Bin; Guo, Daying; Lin, Peirong; Zhou, Ling; Li, Jun; Fang, Guoyong; Wang, Jinyi; Jin, Huile; Chen, Xi'an; Wang, Shun
Abstract: We have successfully constructed a new type of intercalation membrane material by covalently grafting organic tris(hydroxypropyl)phosphine (THPP) molecules onto hydroxylated multi‐walled carbon nanotubes (CNT‐OH) as a functional interlayer for the advanced LSBs. The as‐assembled interlayer has been demonstrated to be responsible for the fast conversion kinetics of polysulfides, the inhibition of polysulfide shuttle effect, as well as the formation of a stable solid electrolyte interphase(SEI) layer. By means of spectroscopic and electrochemical analysis, we further found THPP plays a key role in accelerating the conversion of polysulfides into low‐ordered lithium sulfides and suppressing the loss of polysulfides, thus rendering the as‐designed lithium–sulfur battery in this work a high capacity, excellent rate performance and long‐term stability. Even at low temperatures, the capacity decay rate was only 0.036 % per cycle for 1700 cycles. Abstract : The organic small molecule tris(hydroxypropyl) phosphine (THPP) grafted on hydroxylated multi‐walled carbon nanotubes (CNT‐OH) as intercalation of lithium–sulfur batteries (LSBs) has been demonstrated to accelerate the catalytic conversion, effectively restrain the shuttle effect of polysulfides and reduce the formation of lithium dendrites.